MEMAKSIMALKAN POTENSI DORMANSI PADA ROTIFER Brachionus rotundiformius MELALUI MATING EKSPERIMEN - Warouw, Veibe (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
The rotifer Brachionus sp is widely used in aquaculture as a live prey, but problem remain with less utilization.  It is often difficult to synchronize rotifer production with larvae demand.  Rotifer also produce resting egg with sexual reproduction, this resting egg is thick-walled encysted stages which can remain dorman for extended period.  Used resting egg as a stock can be solved the problem.  With mating eksperiment we found resting egg produced by female rotifer that have not produce egg before.  Suggestion proportion of male and female to produce resting egg is 4 male : 10 female.